Precision Measurement of the Ratio B(t -> Wb)/B(t -> Wq) and Extraction of V-tb - Abazov, V. M.; Abbott, B.; Acharya, B. S.; Adams, M.; Adams, T.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; Alves, G. A.; Aoki, M.; Sajot, G.; et al. (Amer Physical Soc, 2011)
We present a measurement of the ratio of top quark branching fractions R = B(t -> Wb)/B(t -> Wq), where q can be a d, s, or b quark, in the lepton + jets and dilepton t (t) over bar final states. The measurement uses data from 5: 4 fb(-1) of p (p) over bar collisions collected with the D0 detector at the Fermilab Tevatron Collider. We measure R = 0.90 +/- 0.04, and we extract the Cabibbo-Kobayashi-Maskawa (CKM) matrix element vertical bar V-tb vertical bar as vertical bar V-tb vertical bar = 0.95 +/- 0.02, assuming unitarity of the 3 x 3 CKM matrix.